The Development of Teaching Materials Based on Local Wisdom Society Preventing The Radicalism in West Kalimantan - Budiyono Budiyono (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2020)
This research aims to encounter radicalism that is a problem of learning Islam in education institutions in Indonesia through the preparation of local wisdom-based teaching materials in West Kalimantan. The Center for Islamic and Community Studies (PPIM) UIN Jakarta conducted a research on